2009
DOI: 10.1128/jvi.02042-08
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon-Induced Interferon Regulatory Factor 1-Dependent Antiviral Response Inhibits Vaccinia Virus Replication in Mouse but Not Human Fibroblasts

Abstract: Vaccinia virus (VACV) is a prototypical member of the genus Orthopoxvirus of the Poxviridae family (47) and shares more than 90% nucleotide identity with variola virus, the causative virus of smallpox. VACV is the live vaccine used for vaccination against variola virus. Although VACV bears the name resembling the alleged origin species (vacca [Latin for cow]), the natural host of VACV is still elusive (23). In cell culture, VACV can replicate in many cell types (45, 47). Pathogenesis and immune responses have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 81 publications
2
40
0
Order By: Relevance
“…Interestingly, IRF-1 expression was required for IFN-␥-mediated suppression of mouse norovirus (MNV) replication in primary macrophages in vitro (53). A similar phenotype was seen with vaccinia virus (VACV), where IRF-1 was required for IFN-␥-mediated suppression of VACV replication in mouse fibroblasts (54). Because IFN-␥ is not expressed in primary macrophages infected with MHV68 in vitro (our unpublished observations), it is possible that IRF-1 has additional, type I IFN-independent functions that attenuate MHV68 infection, especially in vivo where IFN-␥ is present (55).…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, IRF-1 expression was required for IFN-␥-mediated suppression of mouse norovirus (MNV) replication in primary macrophages in vitro (53). A similar phenotype was seen with vaccinia virus (VACV), where IRF-1 was required for IFN-␥-mediated suppression of VACV replication in mouse fibroblasts (54). Because IFN-␥ is not expressed in primary macrophages infected with MHV68 in vitro (our unpublished observations), it is possible that IRF-1 has additional, type I IFN-independent functions that attenuate MHV68 infection, especially in vivo where IFN-␥ is present (55).…”
Section: Discussionmentioning
confidence: 67%
“…As human IFN␥ does not signal in mouse or rat cells, evidence that microinjection of human IFN␥ elicited antiviral activity in murine cells suggested that the IFNGR provides species specific responses to IFN␥ (31). Further evidence showing that retention of IFN␥ within cells also resulted in an IFN␥-dependent signaling leaded researchers to further claim that the IFNGR drives species specificity responses (32,33).…”
Section: Alternative Mechanisms Regulating the Ifn␥ Signaling Via Endmentioning
confidence: 99%
“…For immunoblotting, cells were lysed (66) and equal amounts of protein were subjected to SDS-PAGE and transferred to nitrocellulose membranes. Immunoblot analysis was performed using mouse monoclonal antibody (MAb) anti-␤-actin (Sigma), mouse MAb recognizing HCMV pUL83/ pp65 (3A12; AbCam), rabbit polyclonal anti-IB␣ (sc-371; Santa Cruz), rabbit MAb anti-phospho-IB␣ (2859; Cell Signaling), rabbit MAb anti-TNFR1 (3736; Cell Signaling), rabbit polyclonal anti-Fas (sc-1023; Santa Cruz), and rabbit polyclonal anti-HA (Sigma).…”
Section: Methodsmentioning
confidence: 99%